REVOLVER: A low-cost automated protein purifier based on parallel preparative gravity column workflows. (April 2022) - Diep, Patrick; Cadavid, Jose L.; Yakunin, Alexander F.; McGuigan, Alison P.; Mahadevan, Radhakrishnan
Graphical abstract: Abstract: Protein purification is a ubiquitous procedure in biochemistry and the life sciences, and represents a key step in the protein production pipeline. The need for scalable and parallel protein purification systems is driven by the demands for increasing the throughput of recombinant protein characterization. Therefore, automating the process to simultaneously handle multiple samples with minimal human intervention is highly desirable, yet there are only a handful of such systems that have been developed, all of which are closed source and expensive. To address this challenge, we present REVOLVER, a 3D-printed programmable protein purification system based on gravity-column workflows and controlled by Arduino boards that can be built for under $130 USD. REVOLVER takes a cell lysate sample and completes a full protein purification process with almost no human intervention and yields results indistinguishable from those obtained by an experienced biochemist when purifying a real-world protein sample. We further present and describe MULTI-VOLVER, a scalable version of the REVOLVER that allows for parallel purification of up to six samples and can be built for under $250 USD. Both systems can help accelerate protein purification and ultimately link them to bio-foundries for protein characterization and engineering.